2003
DOI: 10.1089/107555303322284811
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Way to Individualized Medicine: Psychological and Physical Traits of Sasang Typology

Abstract: Current results demonstrated distinctive personality traits associated with Sasang types using reproducible psychometric and anthropometric instruments. With further study, the Sasang typology could serve as a scientific tool for individualized and integrative medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
179
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(188 citation statements)
references
References 30 publications
7
179
1
1
Order By: Relevance
“…However previous studies have reported the prevalence of the TY type between 0.03% and 0.1% (Chae et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…However previous studies have reported the prevalence of the TY type between 0.03% and 0.1% (Chae et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Jema Lee termed In the view of SCM, the lung, pancreas, liver, and kidney represent a functional system of organ groups that represent respiratory, digestive, preservative, and excretive systems, respectively. This table is modifi ed from Chae et al [5].…”
Section: Classifi Cation Of Human Physical Constitutionmentioning
confidence: 99%
“…these types as Tae-yangin, So-yangin, Tae-eumin, and So-eumin, as shown in Table 1 [5]. This terminology was adopted from the well-known Chinese philosophical writing Book of Changes ( ).…”
Section: Classifi Cation Of Human Physical Constitutionmentioning
confidence: 99%
“…1 Studies have sought to identify distinct characteristics of the four constitutions as a means of best individualizing the treatment approach. [2][3][4][5][6] Generally, the personality traits of the TY type include a creative, positive, progressive temperament, and the type is characterized by hyperactive lung and hypoactive liver functions. The SY type personality is unstable, easily bored, and restrained; this type is more vulnerable to urinary diseases due to hypoactive kidney function.…”
mentioning
confidence: 99%